2016
DOI: 10.1002/ijc.30468
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of multiple primary and combination screening strategies in postmenopausal women for detection of cervical cancer in China

Abstract: As China's population ages, the importance of determining prevalence of cervical disease and accurate cervical cancer screening strategies for postmenopausal women is increasing. Seventeen population-based studies were analyzed to determine prevalence of cervical neoplasia in postmenopausal women. All women underwent HPV DNA testing, visual inspection with acetic acid (VIA) and cytology testing. Diagnostic values for primary and combinations screening methods included sensitivity, specificity, positive predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
3
17
1
Order By: Relevance
“…Our data show that VIA triage of either primary self-careHPV or physician-careHPV testing decreased sensitivity too low for population-based screening programs and suggest that in areas where VIA performance is poor, other biomarkers for cervical precancerous disease should be explored. VIA performance has been shown to improve with provider training (21), and so in areas where VIA performance is currently low, further provider training can be utilized to make the screening strategy of HPVpositive women followed by VIA triage a feasible cervical cancer screening option. Meanwhile, the sensitivity of VIA is also related with the age, which decreases significantly in postmenopausal women compared to premenopausal performance (22).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that VIA triage of either primary self-careHPV or physician-careHPV testing decreased sensitivity too low for population-based screening programs and suggest that in areas where VIA performance is poor, other biomarkers for cervical precancerous disease should be explored. VIA performance has been shown to improve with provider training (21), and so in areas where VIA performance is currently low, further provider training can be utilized to make the screening strategy of HPVpositive women followed by VIA triage a feasible cervical cancer screening option. Meanwhile, the sensitivity of VIA is also related with the age, which decreases significantly in postmenopausal women compared to premenopausal performance (22).…”
Section: Discussionmentioning
confidence: 99%
“…Since more than 90% of cervical cancers are caused by the HPV virus, HPV testing has been suggested as a possible alternative, primary form of cervical cancer screening 10–12. When used in combination with visual inspection with acetic acid (VIA) or Pap smears in low-income settings, HPV testing has been shown to provide significant improvements in the detection of advanced premalignant lesions and cancer in sensitivity as compared with VIA or Pap smear alone, as only women who test positive for HPV need to follow-up with further screening 13–16. Previous studies have also confirmed that HPV self-swab kits are comparable to physician-administered samples in their ability to detect carcinogenic, high-risk HPV 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…Menopause is a life phenomenon with characteristics of estrogen secretion depletion and the cessation of menstruation. The majority of women enter menopause between the ages of 49 and 52 ( Takahashi & Johnson, 2015 ) and some studies show no statistically significant difference in cervical cancer rates of premenopausal and postmenopausal women ( Holt et al, 2017 ; Zhang et al, 2018 ). A total of 8 of the 9 individuals used in this study were premenopausal and the postmenopausal individual was within the age range of normal menopause.…”
Section: Discussionmentioning
confidence: 99%